Herb Pennock : Baseball's Faultless Pitcher - Craig, Keith (Rowman and Littlefield, 2016)
This book tells the life story of Hall of Fame pitcher Herb Pennock (1894-1948), considered one of the best left-handed pitchers in the history of the game. He pitched for the dynastic 1920s New York Yankees, won 241 games, never lost in the World Series, and came within four outs of pitching the first no-hitter in a World Series in 1927. Herb Pennock features interviews with family and friends, as well as never-before-seen photographs of Pennock and his baseball buddies.